TXLNG improves insulin resistance in obese subjects in vitro and in vivo by inhibiting ATF4 transcriptional activity. (1st June 2023) - Tao, Jing; Gu, Peipei; Lai, Hongmei; Peng, Hui; Guo, Zitong; Yuan, Yujuan; Yu, Xiaolin; Shen, Xin; Liu, Jun; Xier, Zulipiyemu; Li, Guoqing; Yang, Yining
Abstract: Lipotoxicity contributes to insulin resistance and dysfunction of pancreatic β-cells. Insulin promotes 3T3-L1 preadipocyte differentiation and facilitates glucose entry into muscle, adipose, and other tissues. In this study, differential gene expression was analyzed using four datasets, and taxilin gamma (TXLNG) was the only shared downregulated gene in all four datasets. TXLNG expression was significantly reduced in obese subjects according to online datasets and in high-fat diet (HFD)-induced insulin-resistant (IR) mice according to experimental investigations. TXLNG overexpression significantly improved IR induced by HFD in mouse models by reducing body weight and epididymal adipose weight, decreasing mRNA expression of pro-inflammatory factors interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α), and reducing adipocyte size. High-glucose/high-insulin-stimulated adipocytes exhibited decreased TXLNG and increased signal transducer and activator of transcription 3 (STAT3) and activating transcription factor 4 (ATF4). IR significantly decreased glucose uptake, cell surface glucose transporter type 4 (GLUT4) levels, and Akt phosphorylation, while increasing the mRNA expression levels of IL-6 and TNF-α in adipocytes. However, these changes were significantly reversed by TXLNG overexpression, while they were exacerbated by TXLNG knockdown. TXLNG overexpression had no effect on ATF4 protein levels, while ATF4 overexpression increased ATF4 protein levels. Furthermore, ATF4 overexpression notably abolished the improvements in IR adipocyte dysfunction caused by TXLNG overexpression. In conclusion, TXLNG improves IR in obese subjects in vitro and in vivo by inhibiting ATF4 transcriptional activity. Highlights: TXLNG overexpression improves HFD-induced insulin resistance in mice. TXLNG overexpression attenuates the resistance of mature adipocytes to insulin. TXLNG affects adipocyte IR by modulating ATF4 transcriptional activity.